1H-indole-based chemosensors for the sequential recognition of Hg2+ and CN− ions. (26th March 2021) - Sayapin, Yury A.; Gusakov, Eugeny A.; Tupaeva, Inna O.; Karlutova, Olga Yu; Dubonosova, Irina V.; Tkachev, Valerii V.; Starikov, Andrey G.; Dubonosov, Alexander D.; Aldoshin, Sergey M.
Abstract: Сhemosensors based on 1 H -indole, 1 H -benzo[ e ]indole, and 1 H -benzo[ g ]indole were synthesized. According to 1 H, 13 C NMR, X-ray diffraction study and DFT calculations, they exist predominantly in keto form, which absorbs at 371–404 nm and exhibit a low-intensity fluorescence at 454–527 nm. Recognition of Hg 2+ cations in acetonitrile results in a bathochromic shift of the long-wave absorption band by ∼20 nm, accompanied by a "naked-eye" effect that causes the colorless solution to turn bright yellow. At the same time, the emission of sensors is completely quenched. The in situ mercury(II) complexes sequentially and selectively detect CN − anions with full restoration of the initial absorption and fluorescence spectra. The fluorescence "on–off–on" cycles generated by the consistent addition of Hg 2+ and CN − ions provide the obtained compounds with the properties of ionochromic molecular switch. The values of the limit of detection are 1.8 and 0.83 μМ for Hg 2+ and CN − ions, respectively. Graphical abstract: Image 1 Highlights: Novel 1 H -(benzo)indole chemosensors were synthesized. They are capable to detect Hg 2+ ions via the "naked-eye" effect and emission quenching. The in situ formed mercury(II) complexes sequentially and selectively recognize CN − anions. The consistent addition of Hg 2+ and CN − ions leads to "on–off–on" fluorescence cycles.